An experimental study of the performance of low-molecular weight polymer for enhanced heavy oil recovery in a heterogeneous media. Issue 2 (4th March 2018) - Ghahremani, Hossein; Mobaraki, Sina; Khalilinezhad, Seyyed Shahram; Jarrahian, Khosrow
Abstract: The goal of enhanced oil recovery is to improve sweep efficiency in the reservoir by the injection of artificial materials in order to reduce the trapped oil saturation. In this study, the application of an anionic polyacrylamide polymer was investigated for heavy oil recovery based on the results of rheological measurements and oil recovery experiments. The properties of the polymer solution were interpreted by the use of well-known rheological models and oil recovery experiments were performed using a heterogeneous two-dimensional glass micromodel saturated with heavy oil of 270 cP. To provide a better understanding of the microscopic efficiency of the process, analysis of continuously provided pictures during the experiments by the use of image processing technique was performed. Rheological results combined with microscopic observations revealed that the non-Newtonian behavior of the solution enhances the sweep efficiency of the both pore throats and pore bodies. Macroscopic observations showed the ultimate oil recovery of 56% and dramatic improvement in breakthrough time during polymer flood in comparison to water flood. In addition, the microscopic pictures disclosed that the pulling effect and stripping mechanisms are responsible mechanisms for the high microscopic sweep efficiency during polymer flooding.